Twelve loci from HSA10, HSA11 and HSA20 were comparatively FISH-mapped on river buffalo and sheep chromosomes - Iannuzzi, L.; Gallagher, D. S.; Di Meo, G. P.; Schlapfer, J.; Perucatti, A.; Amarante, MRV; Incarnato, D.; Davis, S. K.; Taylor, J. F.; Womack, J. E. (Karger, 2001)
Ten type I loci from HSA 10 (IL2RA and VIM), HSA11 (HBB and FSHB) and HSA20 (THBD, AVP/OXT, GNAS1, HCK and TOP1) and two domestic cattle type II loci (CSSM30 and BL42) were FISH mapped to R-banded river buffalo (BBU) and sheep (OAR) chromosomes. IL2RA (HSA 10) maps on BBU 14q13 and OAR13q13, VIM (HSA 10) maps on BBU14q15 and OAR13q15, HBB (HSA11) maps on BBU16q25 and OAR15q23, FSHB (HSA11) maps on BBU16q28 and OAR15q26. THBD (HSA20) maps on BBU 14q15 and OAR13q15 while AVP/OXT. GNAS1, HCK, and TOP I (HSA20) as well as CSSM30 and BL42 map on the same large band of BBU 14q22 and OAR13q22. All loci were mapped on the same homologous chromosomes and chromosome bands of the two species, and these results agree with those earlier reported in cattle homologous chromosomes 15 and 13. respectively, confirming the high degree of both banding and physical map similarities among the bovid species. Indirect comparisons between physical maps achieved on bovid chromosomes and those reported on HSA10, HSA11 and HSA20 were performed. Copyright (C) 2001 S. Karger AG, Basel.